# Topic: Special Products

Prerequisite Concepts: Multiplication and Division of Polynomials
About the Lesson: This is a very important lesson. The applications come much later but the skills will always be useful from here
on.
Objectives:
In this lesson, you are expected to: find algebraically the
1. Product of a sum and difference of two terms
2. Square of a binomial
3. Cube of a binomial
4. Product of a binomial and a trinomial

A. Product of a sum and difference of two terms
I. Activity
Use FOIL method to find the product of the following:
a. (x + 1) (x – 1) =
b. (x + 3) (x – 3) =
c. (2x – 1) (2x + 1) =
d. (2x – 3) (2x + 3) =

II. Questions to Ponder
1. What are the products?
2. What is the common characteristic of the factors in the activity?
3. Is there a pattern for the products for these kinds of factors? Give the rule.

Description of the product of a sum and difference:
In words: The product of the sum and the difference of the same two terms is the difference of their squares.
Algebraically: (a+b)(a-b) = a2 - b2
Example: (x+2)(x-2) = x2 - 22 = x2 - 4

I. Exercises
Find the product of each of the following:
1. (x – 5) (x + 5) 6. (x2 – 10)(x2 + 10)
2. (x + 2) (x – 2) 7. (4xy + 3z3) (4xy – 3z3)
3. (3x – 1) (3x + 1) 8. (3x3 – 4)(3x3 + 4)
4. (2x + 3) (2x – 3) 9. [(x + y) - 1] [(x + y) + 1]
5. (x + y2) (x – y2) 10. ((2x + y) – z) ((2x + y) + z)
B. Square of a binomial
Activity
Use the FOIL method; find the product of the following:
a. (x + 3) (x + 3) =
b. (x – 2) (x – 2) =
c. (2x + 1) (2x + 1) =
d. (2x – 1) (2x – 1) =
Description of the square of a Binomial:
In words: Square the first term, add twice the product of the terms, add the square of the last term.
Algebraically: (a+b) 2 = a2 + 2ab + b2 , (a-b) 2 = a2 - 2ab + b2
2 2
Example: (x + 4) = x + 8x + 16 , (x - 3) 2 = x2 - 6x + 9

II. Exercises
Find the squares of the following binomials.
1. (x + 5)2 =
2. (x - 5)2 =
2
3. (x + 4) =
2
4. (x – 4) =
5. (2x + 3)2 =

(3x – 4y ) = C. (x + 3) ( x2 .3p + 9) = 2 7. (h . (3x . (4 – 5x)2 = 2 8.b)3 = (a3 . (p + 2) 3 = 7.3a2b + 3ab2 . add twice the product of the terms. (2p + 3) 3 = 9. (2x + 5)(4x2 – 10x + 25) = 3. Multiply 3 to the square of the first term and also multiply 3 to the first term times the square of the second term to get the two middle terms of the product.5x +25) = b. (x + 10)(x2 – 10x + 100) = 2 4.27 II. (x + 5) (x2 .ab + b2) = a3 + b3 2 3 Example: (x . (1 + 9x) = 9.10) 3 = 4. (p + 1) 3 = . (a+b) ( a2 .2)2 = 7. (3x .6)( x + 6x + 36) = 5. (2x . Sum and difference of two cubes Find the product of the following using distributive method: a.2x + 4) = c.4) 3 = 2.2) (y2 + 2x + 4) = Sum and difference of two cubes: In words: Square the first term.2)(g2 + 2g + 4) = 2 9.5)3 = 3.b) 3 = Cube of binomial In words: Find the cube of each term to get the first term and the last term of the product. (x + 6) 3 = 5. (3x + 4)(9x2 – 12x + 16) = 2. (3x . (y .1) 3 = 10.135x2 + 225xy2 – 125y3 1. (x2 + 3y)2 = 3 2 2 10.1) 3 = 6. add the square of the last term.4) (x + 4x + 16) = x + 64 . 1. (y + 2) (y2 . (a .b3 . (x .1)(h + h + 1) = D.6. (x .5y) 3 = 27x3 . Algebraically: (a-b) ( a2 + ab + b2) = a3 . Exercises Find the Sum and difference of two cubes.5) (x2 + 5x +25) = d.4) 3 = 8. (p + 3)(p2 . (3x .b3) 3 3 2 Example: (2a + 3) = 8a + 36a + 54a + 27 . (3x . (3x . (g . (2f .2)(4f + 4f + 4) = 8. (3h + 2)(h . Formula: (a + b)3 = ( a3 + 3a2b + 3ab2 + b3) . (x . Cube of binomial Find the expanded form of the following expressions: (a + b) 3 = (a .3x + 9) = x3 .6h + 4) = 2 10. (x .4)( 9x2 + 12x + 16) = 6.